The psychology of religion and coping : theory, research, practice - Pargament, Kenneth I. (Kenneth Ira), 1950- (Guilford Press, 1997)
"When faced with a crisis, why do some people turn to religion to help them cope, while others turn away? Is religious belief merely a defense or a form of denial? Is religion a help or a hindrance in times of stress? Building a much-needed bridge between two different worlds of thought and practice - religion and psychology - this volume sensitively interweaves theory with first-hand accounts, clinical insight, and empirical research. The book underscores the need for greater sensitivity to religion and spirituality in the context of helping relationships and suggests several ways clinicians can work more effectively with religious issues in therapy." "Providing a rich, in-depth analysis of the role of spiritually and sacredness in the coping process, the author breaks free of limiting stereotypes to explore specific ways that religious belief may be helpful or harmful in the search for significance." "A vital source of information and direction for mental health practitioners, psychology researchers, and religious professionals and educators, the book also serves as a text for courses dealing with the interface of religion, psychology, and mental health."--Jacket.